Implementasi Dwangsom sebagai Upaya Paksa dalam Mewujudkan Kepastian Hukum bagi Pelaksanaan Putusan PTUN - Chintya Ruth Arini Purba; Wahyu Andrianto (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The State Administrative Court, as an absolute prerequisite for the realization of good governance in a government system, should have a decision that can always be implemented by the losing Defendant so that actions or decisions that harm the community can be immediately corrected, revoked, and a new decision issued by the Government as Defendant. However, in practice, this decision from the TUN Court often needs to be obeyed or implemented. In fact, the Administrative Court Law has provided for the execution of a verdict that Defendant has not implemented within a certain period of time. Particularly in condemnatory decisions, the Administrative Court Law provides coercive measures in the form of dwangsom or forced money to force the Defendant to comply with the decision of the State Administrative Court. Until now, the dwangsom mechanism is still unclear and has resulted in differences in the mechanism for imposing dwangsom by the Panel of Judges who decided on the payment of the dwangsom, which in fact, creates legal uncertainty in the implementation and regulation of dwangsom. Therefore, this analysis will discuss in depth the mechanism for submitting and requesting the imposition of dwangsom, including discussing the Defendants who may be subject to the burden of paying dwangsom.